A STUDY OF ESTIMATION OF STATURE FROM HAND MEASUREMENTS: A CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Stature estimation from partial remains is a critical component of forensic identification and disaster victim management. Hand dimensions, particularly hand length and breadth, have emerged as practical predictors of stature in diverse populations. Objective: To determine the relationship between stature and hand dimensions among young Indian adults and to derive regression equations for stature estimation from hand length and selected finger measurements. Methods: A cross-sectional study was conducted among a mixed-sex sample of medical students aged 18–25 years at a Government Medical College in Andhra Pradesh, India. Anthropometric measurements included stature, weight, BMI, right- and left-hand length, right- and left-hand breadth, and the lengths of individual fingers on both hands, recorded using standard anthropometric instruments. After cleaning biologically implausible entries, descriptive statistics, Pearson correlation, and simple linear regression were performed. The results were interpreted in conjunction with recent international literature on hand-based stature estimation. Results: A total of 308 participants (approximately equal proportions of males and females) were analyzed. Mean stature was 164.07 ± 9.14 cm, and mean BMI was 22.53 ± 4.31 kg/m². Mean right- and left-hand lengths were 17.79 ± 1.19 cm and 17.81 ± 1.19 cm, respectively. Stature showed a strong positive correlation with left-hand length (r = 0.817, p < 0.001) and right-hand length (r = 0.811, p < 0.001). Among finger measurements, left ring finger length (r = 0.712) and left middle finger length (r = 0.705) showed the strongest associations with stature. The best single-predictor regression model for stature was based on left hand length, Height (cm) = 55.98 + 6.03 × Left hand length (cm), with R² = 0.668 and mean absolute error (MAE) 4.07 cm; right hand length yielded a similar model with R² = 0.657. Conclusion: Hand length is a robust predictor of stature in young Indian adults from Andhra Pradesh, with left- and right-hand lengths providing practical regression equations suitable for forensic casework. These findings align with recent Asian and international studies and underscore the necessity of population-specific algorithms for forensic stature estimation. However, these findings are based on a single-centre sample of young medical students and a restricted age range of 18–25 years, which may limit generalizability to other age groups and populations. Future studies in broader, community-based cohorts are needed to validate and refine these regression equations.